Factors Influencing Teenagers Understanding on Electronic Information and Transaction Law Implementation in the Cyberspace: A Psychoanalysis Perspective - Rahayu, Aneke Dewi; Andamari, Sri Respati (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2021)
The development of science and technology impacts changes in the order of human life, especially teenagers. Teenagers today tend to prefer using technology in interacting with one another. This activity is known as cyberspace. Cyberspace is a place for technology users, especially teenagers, to express pleasure, displeasure, and other activities. These activities can be analyzed using Freud's psychoanalytic theory, which includes three structures, namely: id, ego, and superego. The id possessed by a person has the principle of pleasure, while the ego is described through individual activities aimed at gaining recognition, while the superego is the controller of the id and ego so that a person has moral behavior. Concerning cyberspace, a teenager is expected to understand the laws and regulations as stated in the Information and Electronic Transactions Law (UU ITE or ITE Law). The purpose of this study aims to determine the factors that influence the level of understanding of adolescents about the UU ITE from a psychoanalytic perspective. This study uses a mix-method approach by combining FGD and scale in obtaining data. The data were analyzed using an exploratory factor analysis approach. This study shows that six valid factors with an eigenvalue of 60.36% influence adolescents in understanding the ITE Law. The six factors include socialization, media used, content quality, socialization agents, personal character, and conditional.